Loneliness and cannabis use among older adults: findings from a Canada national survey during the COVID-19 pandemic - Li, Lun; Deng, Qian (My University, 2024)
Background: Cannabis use has been increasing among older adults in Canada, particularly during the COVID-19 pandemic. This study aims to examine the association between loneliness and cannabis use among older Canadians during the pandemic. Methods: Quantitative data analyses were performed based on 2,020 participants aged 55 years and older from the Canadian Perspectives Survey Series 6, 2021: Substance Use and Stigma During the Pandemic. Results: This study found that participants who used cannabis in the 30 days before the survey reported significantly higher loneliness scores than those who never used cannabis after adjusting social-demographic, social interaction, and pandemic-related factors. Participants who kept using cannabis during the pandemic also reported significantly higher loneliness scores than those who never used cannabis. Conclusion: The findings about the correlation between cannabis use and greater loneliness contribute to the discourse on potential health and wellbeing harms of cannabis use among older adults.
Keywords: loneliness; cannabis use; healthy aging